Synchrotron X-Ray Absorption Spectroscopy Study of Self-Assembled Nanoparticles Synthesized from Fe(acac)3 and Pt(acac)2. (23rd August 2011) - Chokprasombat, K.; Sirisathitkul, C.; Harding, P.; Chandarak, S.; Yimnirun, R.
Abstract : The synchrotron X-ray absorption technique was used to complement electron microscopy in the investigation of nanoparticles synthesized from the coreduction of iron acetylacetonate, Fe(acac)3 and platinum acetylacetonate, Pt(acac)2 . A much higher Pt composition than Fe leads to an extended X-ray absorption fine structure (EXAFS) spectrum for the sample that differs from that of fcc FePt nanoparticles. Most importantly, X-ray absorption near-edge structure (XANES) spectra clearly indicate the existence of α -Fe2 O3 and Pt metal. Since these monodisperse nanoparticles have a diameter of around 4 nm and tend to self-assemble into hexagonal arrangements, they can be modeled as Pt-rich cores with an α -Fe2 O3 shell stabilized by organic surfactants.